2021
DOI: 10.3390/polym13050705
|View full text |Cite
|
Sign up to set email alerts
|

Polypropylene/Ethylene—And Polar—Monomer-Based Copolymers/Montmorillonite Nanocomposites: Morphology, Mechanical Properties, and Oxygen Permeability

Abstract: This research reports the influence of polar monomer contents in ethylene vinyl acetate copolymer (EVA) and ethylene vinyl alcohol copolymer (EVOH) on the morphology, mechanical and barrier properties of polypropylene/ethylene copolymer (PP) reinforced with organically modified montmorillonite (MMT). PP/EVA and PP/EVOH (75/25 wt %) blends were reinforced with 3 wt % MMT in an internal mixer system. Samples were compression-molded into films of 300μ μm. The structural characterization was made using X-ray diffr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 17 publications
(5 citation statements)
references
References 53 publications
0
4
0
1
Order By: Relevance
“…Table 3 shows the Young's modulus, elongation at break and tensile strength of various polymeric blends and nanocomposites samples studied by Castro-Landinez et al [136]. A 21% increase in stiffness was seen for blends with EVA28 while it was 15% with EVA12 as compared with EVOH systems.…”
Section: Mechanical Properties Of Mmt/natural Fiber Reinforced Polyme...mentioning
confidence: 96%
See 1 more Smart Citation
“…Table 3 shows the Young's modulus, elongation at break and tensile strength of various polymeric blends and nanocomposites samples studied by Castro-Landinez et al [136]. A 21% increase in stiffness was seen for blends with EVA28 while it was 15% with EVA12 as compared with EVOH systems.…”
Section: Mechanical Properties Of Mmt/natural Fiber Reinforced Polyme...mentioning
confidence: 96%
“…The results demonstrated that the MMT showed better interactions with PP/EVA blends because they operate as a reinforcing agent than the effect on the PP/EVOH blends. Interestingly, with the introduction of clay into polymeric blends for both PP/EVA and PP/EVOH, the elongation at break and the tensile strength showed no significant change [136]. Shikaleska et al [137] reported that poly(ethylmethacrylate) (PEMA) and MMT clay particles have a considerable effect on the mechanical properties of poly(vinylchloride) (PVC)/PEMA 90/10 blend composite.…”
Section: Mechanical Properties Of Mmt/natural Fiber Reinforced Polyme...mentioning
confidence: 99%
“…Es importante mencionar que, existen empaques que presentan una serie de defectos, como bajas propiedades antimicrobianas, alta permeabilidad al oxígeno y/o a la humedad, que pueden solucionarse añadiendo un componente de refuerzo (Hsissou et al, 2021;Nejatian et al, 2023), y que según Kim et al (2021) pueden modificar las propiedades de permeabilidad en los envases en función de la temperatura, reduciendo así los efectos perjudiciales del gas en el interior de los productos envasados, como la aceleración de la maduración y la reducción de la vida útil de los productos frescos. Por ejemplo, Castro-Landinez et al (2021) indican que el EVOH es muy conocido como material polimérico de baja permeabilidad al oxígeno; entre 0,4 a 3 cm 3 ꞏmm/m 2 ꞏdayꞏatm que, agregándole al PP mejora la barrera al oxígeno, a diferencia del etileno acetato de vinilo (EVA) tiene una permeabilidad al oxígeno mayor, que oscila entre 800 a 1000 cm 3 ꞏmm/m 2 ꞏdayꞏatm, los cuales son superiores a los reportados en el presente trabajo.…”
Section: Resultado Y Discusiónunclassified
“…In general, inorganic silicones are mainly used as adjuvants in combination with other FRs for PO polymers. Among them, SiO 2 [ 54 , 55 ] and MMT are the most commonly used inorganic silicone adjuvants [ 56 , 57 ]. Thus, this section mainly discusses these two types of FRs.…”
Section: Inorganic Flame Retardantsmentioning
confidence: 99%